KAJIAN TERHADAP PERILAKU PENGGUNA SISTEM INFORMASI MENGGUNAKAN MODEL UTAUT - Diana, Diana (JURNAL ILMIAH MATRIK, 2013)
This research, review of behavioral intention and use behavior of users of information systems by using UTAUT Model. Respondents were employees in the city of Palembang males (63.3%) and females (36.66%) from 120 respondents. The questionnaire has a scale of 1 to 5 (five-point Liker scale), as a means of gathering data to see relationships influence of independent variables and the dependent variable. Independent variables are performance expectancy, effort expentancy, social influence and facilitating condition. Then, dependent variable are behavioral intention and use behavioral. The result, performance expectancy, effort expentancy has a positive and significant correlation with behavioral intention , while social influence has no correlation. F test show performance expectancy, effort expentancy and social influence has a correlation to behavioral intention. Facilitating condition and behavioral intention of partially and simultaneously correlated to use behavioral. Simultaneously to test behavioral intention and use behavioral are 53% and 64.3%. Keywords: UTAUT Model, Information System, , Behavioral Intention, and Use Behavioral